A production process of o-nitrochlorobenzene
By combining the supported heteropolyacid catalyst and the nitrifying agent, problems such as waste acid production and difficult product separation in the traditional sulfuric acid catalyst process are solved, the yield and selectivity of nitrified chlorobenzene are improved, and the production of high-purity ortho-nitrobenzene chloride is achieved.
Patent Information
- Application Number
- CN202411944372.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-01
AI Technical Summary
In the prior art, the nitration process of sulfuric acid as a catalyst has problems such as waste acid generation, difficulty in separation of products, and equipment corrosion, and the yield of nitrated chlorobenzene is low, making it difficult to effectively improve.
The selectivity and yield of nitrated chlorobenzene are improved by using a process of combining a supported heteropolyacid catalyst with a nitrifying agent.
The production of high-purity ortho-nitrobene chloride is achieved, with a yield of 90.86%, and the ratio of /o-isomer is optimized, the catalyst performance is stable, and it is easy to reuse.
Smart Images

Figure BDA0005213291850000141 
Figure BDA0005213291850000151
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nitrochlorobenzene preparation, and specifically relates to a production process of o-nitrochlorobenzene. Background Art
[0002] o-Nitrochlorobenzene is an important organic chemical raw material, which is widely used in dyes, medicines, pesticides and other fields. Therefore, it is of great practical significance to study the manufacturing method of o-nitrochlorobenzene. At present, the traditional process of nitration of chloronitrobenzene in my country's industry is mainly based on mixed acid composed of nitric acid and sulfuric acid. This process has been used for more than a century and has been the main means of nitration of chlorobenzene. A relatively mature nitration theory system has been formed. However, the traditional nitration process has many disadvantages: (1) sulfuric acid is used as a catalyst, and a large amount of waste acid is generated during the reaction, which is difficult to recover and treat; (2) sulfuric acid is not easy to separate from the product and the separation process consumes a lot of energy; (3) sulfuric acid is highly corrosive and easily corrodes equipment and instruments. In addition, due to the electronic effect of halogen atoms, halogen atoms are special electron-withdrawing ortho-para-directing groups on the aromatic ring. This method produces a mixture of o-nitrochlorobenzene and p-nitrochlorobenzene. Generally, p-chloronitrobenzene is the main product, and the yield of o-nitrochlorobenzene is very low.
[0003] Based on this, we proposed a production process of o-nitrochlorobenzene, hoping to solve the shortcomings of the existing technology, thereby improving the selectivity of the nitration product and increasing the yield of o-nitrochlorobenzene. Summary of the invention
[0004] The purpose of the invention is to provide a production process of o-nitrochlorobenzene in view of the existing problems.
[0005] The present invention is achieved through the following technical solutions:
[0006] A production process of o-nitrochlorobenzene comprises the following steps:
[0007] S1. Add the supported heteropoly acid catalyst, chlorobenzene, carbon tetrachloride and nitrating agent into a three-necked flask in sequence, and react at a constant temperature of 35-45° C. for 3-6 hours. After the reaction is completed, cool to room temperature and separate the supported heteropoly acid catalyst by vacuum filtration;
[0008] S2. Allow the mixture to stand for stratification, wash the organic layer with a 5% NaHCO3 aqueous solution until it becomes neutral, and then dry it in a vacuum drying oven until it becomes constant weight, and then separate and crystallize it to obtain o-nitrochlorobenzene.
[0009] Preferably, the preparation of the supported heteropolyacid catalyst in step S1 comprises the following steps:
[0010] (1) Anhydrous ethanol and deionized water are prepared into an ethanol solution in a ratio of 5:1, montmorillonite is added into an ultrafine grinder for ultrafine grinding, and then passed through a 400-mesh sieve, and then added into the above ethanol solution, after ultrasonic dispersion, 1 mol / L hydrochloric acid solution is added while stirring, the pH is adjusted to 3-4, and then γ-aminopropyltriethoxysilane is added, and the mixture is stirred at a constant temperature of 70-80°C and 200-300 rpm for reaction for 8-12 hours, and then centrifuged, and the precipitate is collected and dried to obtain modified montmorillonite;
[0011] (2) Dissolve chitosan in 1% glacial acetic acid solution, adjust the pH to 4.5, add tannic acid solution, stir at 200-300 rpm for 20-30 min, add titanium tetrachloride solution, stir at 600-800 rpm for 2-3 h, let stand for 5-6 h, filter, wash with deionized water 3-5 times, and freeze-dry to obtain modified chitosan for later use;
[0012] (3) Dissolve the modified chitosan in 1% glacial acetic acid solution, adjust the pH to 5, ultrasonically disperse the modified montmorillonite in deionized water to obtain a suspension, dropwise add the modified chitosan glacial acetic acid solution to the modified montmorillonite suspension at a rate of 50 mL / L, stir at 800-1000 rpm for 10-16 min, heat to 60-70° C. and react for 18-20 h. After the reaction is completed, filter and wash with deionized water until the pH is neutral, filter and then place in a vacuum drying oven at 50-60° C. and dry for 24-48 h to obtain a chitosan-montmorillonite composite;
[0013] (4) The chitosan-montmorillonite composite is refluxed in a heteropolyacid aqueous solution for 8 to 10 hours, filtered, and the filter cake is washed with deionized water until neutral, and then dried at 40 to 50° C. in a vacuum drying chamber for 24 to 48 hours, and then calcined at 200° C. for 2 to 3 hours to obtain the desired supported heteropolyacid catalyst.
[0014] Preferably, the speed of the ultrafine pulverizer in step (1) is 5000-6000 rpm.
[0015] Preferably, the weight volume ratio of the montmorillonite to the ethanol solution in step (1) is 1 g:30 mL;
[0016] The weight volume ratio of the montmorillonite to the hydrochloric acid solution is 1 g:100 mL;
[0017] The weight-to-volume ratio of the montmorillonite to gamma-aminopropyltriethoxysilane is 1 g:1 mL.
[0018] Preferably, the weight-to-volume ratio of the chitosan to the glacial acetic acid solution in step (2) is 1 g:100 mL;
[0019] The concentration of the tannic acid solution is 3-4 mg / mL, and the addition amount is 1%;
[0020] The concentration of the titanium tetrachloride solution is 0.2-0.3 mol / L, and the addition amount is 1%.
[0021] Preferably, the weight volume ratio of the modified chitosan and the glacial acetic acid solution in step (3) is 1 g:100 mL;
[0022] The weight volume ratio of the modified montmorillonite to deionized water is 1 g:30 mL;
[0023] The volume ratio of the modified chitosan glacial acetic acid solution to the modified montmorillonite suspension is 1:2-3.
[0024] Preferably, the heteropoly acid described in step (4) is one of phosphotungstic heteropoly acid, phosphomolybdic acid and silicotungstic acid.
[0025] Preferably, the nitrating agent in step S1 is sulfuric acid-nitric acid-phosphoric acid, and the ratio of sulfuric acid, nitric acid and phosphoric acid is 2:2:6.
[0026] Preferably, the ratio of chlorobenzene, nitrating agent and carbon tetrachloride in step S1 is 1:2:5-8;
[0027] The weight-to-volume ratio of the supported heteropolyacid catalyst to the nitrating agent is 1 g:2-20 mL.
[0028] Preferably, the drying temperature in step S2 is 50-60°C.
[0029] Compared with the prior art, the present invention has the following advantages:
[0030] The invention provides a production process of o-nitrochlorobenzene. Chlorobenzene and a nitrating agent are used as raw materials, and a reaction is carried out under the action of a supported heteropoly acid catalyst. After separation, crystallization and other post-treatment means, high-purity o-nitrochlorobenzene is obtained. The supported heteropoly acid catalyst and the nitrating agent cooperate with each other to improve the yield, promote the synthesis of o-nitrochlorobenzene, the to-ortho ratio reaches 0.95, and the yield is as high as 90.86%.
[0031] Firstly, the ultrafinely crushed and sieved montmorillonite is acidified to increase the specific surface area and total porosity of the montmorillonite, and the adsorption capacity is increased accordingly. Then, it is reacted with γ-aminopropyltriethoxysilane in a suitable proportion. γ-aminopropyltriethoxysilane reacts with the hydroxyl groups on the montmorillonite to form hydrogen bonds and synthesize covalent bonds, thereby improving the structure and properties of the montmorillonite.
[0032] Secondly, tannic acid is grafted onto chitosan through an amidation reaction, which improves the stability and adsorption of chitosan, and can also change the physical structure of chitosan, and then form a metal-polyphenol structure with titanium tetrachloride to improve the catalytic activity of the catalyst.
[0033] Finally, the modified chitosan and the modified montmorillonite are prepared into a composite with uniform particle size distribution, stable performance and large specific surface area according to a certain ratio, and the composite is used as a carrier to load the heteropoly acid. The catalyst can not only avoid acid corrosion, improve catalytic activity, and increase the yield and purity of the product, but also cooperate with the nitrating agent to reduce the ratio of the para / ortho isomers of the nitration product, which is conducive to the generation of the ortho nitro isomer. In addition, the catalyst of the present invention has stable performance, has the advantages of repeated use and easy separation of the product. DETAILED DESCRIPTION
[0034] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example 1
[0036] A production process of o-nitrochlorobenzene comprises the following steps:
[0037] S1. Add the supported heteropoly acid catalyst, chlorobenzene, carbon tetrachloride and nitrating agent into a three-necked flask in sequence, and react at a constant temperature of 35° C. for 3 h. After the reaction is completed, cool to room temperature and separate the supported heteropoly acid catalyst by vacuum filtration;
[0038] The nitrating agent is sulfuric acid-nitric acid-phosphoric acid, and the ratio of sulfuric acid, nitric acid and phosphoric acid is 2:2:6;
[0039] The ratio of chlorobenzene, nitrating agent and carbon tetrachloride is 1:2:5;
[0040] The weight volume ratio of the supported heteropolyacid catalyst to the nitrating agent is 1 g:2 mL;
[0041] S2. Allow the layers to stand and separate, wash the organic layer with a 5% NaHCO3 aqueous solution until it becomes neutral, dry it in a vacuum drying oven at 50°C until it becomes constant weight, separate and crystallize it to obtain o-nitrochlorobenzene.
[0042] The preparation of the supported heteropolyacid catalyst described in step S1 comprises the following steps:
[0043] (1) Anhydrous ethanol and deionized water are prepared into an ethanol solution in a ratio of 5:1, 1 g of montmorillonite is added into an ultrafine grinder at 5000 rpm for ultrafine grinding, and then passed through a 400 mesh sieve, and then added into 30 mL of the above ethanol solution, and after ultrasonic dispersion, 100 mL of hydrochloric acid solution (1 mol / L) is added while stirring, and the pH is adjusted to 3, and then 1 mL of γ-aminopropyltriethoxysilane is added, and the mixture is stirred at 70°C and 200 rpm for 8 h, and then centrifuged, and the precipitate is collected and dried to obtain modified montmorillonite;
[0044] (2) Dissolve 1 g of chitosan in 100 mL of 1% glacial acetic acid solution, adjust the pH to 4.5, add 1% tannic acid solution (3 mg / mL), stir at 200 rpm for 20 min, add 1% titanium tetrachloride solution (0.2 mol / L), stir at 600 rpm for 2 h, let stand for 5 h, filter, wash with deionized water 3 times, and freeze-dry to obtain modified chitosan for later use;
[0045] (3) Dissolve 1 g of modified chitosan in 100 mL of 1% glacial acetic acid solution, adjust the pH to 5, ultrasonically disperse 15 g of modified montmorillonite in 450 mL of deionized water to obtain a suspension, drop the modified chitosan glacial acetic acid solution into the modified montmorillonite suspension at a rate of 50 mL / L, stir at 800 rpm for 10 min, heat to 60 ° C and react for 18 h, filter after the reaction is completed, wash with deionized water until the pH is neutral, filter, and then place in a vacuum drying oven at 50-60 ° C for 24 h to obtain a chitosan-montmorillonite composite;
[0046] The volume ratio of the modified chitosan glacial acetic acid solution to the modified montmorillonite suspension is 1:2~;
[0047] (4) The chitosan-montmorillonite composite was refluxed in an aqueous solution of phosphotungstic heteropolyacid for 8 h, filtered, and the filter cake was washed with deionized water until neutral, then dried at 40° C. in a vacuum drying chamber for 24 h, and calcined at 200° C. for 2 h to obtain the desired supported heteropolyacid catalyst.
[0048] Example 2
[0049] A production process of o-nitrochlorobenzene comprises the following steps:
[0050] S1. Add the supported heteropoly acid catalyst, chlorobenzene, carbon tetrachloride and nitrating agent into a three-necked flask in sequence, and react at a constant temperature of 40° C. for 5 h. After the reaction is completed, cool to room temperature and separate the supported heteropoly acid catalyst by vacuum filtration;
[0051] The nitrating agent is sulfuric acid-nitric acid-phosphoric acid, and the ratio of sulfuric acid, nitric acid and phosphoric acid is 2:2:6;
[0052] The ratio of chlorobenzene, nitrating agent and carbon tetrachloride is 1:2:6;
[0053] The weight volume ratio of the supported heteropolyacid catalyst to the nitrating agent is 1 g:10 mL;
[0054] S2. Allow the layers to stand and separate, wash the organic layer with a 5% NaHCO3 aqueous solution until it becomes neutral, dry it in a vacuum drying oven at 55°C until it becomes constant weight, separate and crystallize to obtain o-nitrochlorobenzene.
[0055] The preparation of the supported heteropolyacid catalyst described in step S1 comprises the following steps:
[0056] (1) Anhydrous ethanol and deionized water are prepared into an ethanol solution in a ratio of 5:1, 1 g of montmorillonite is added into an ultrafine grinder at 5500 rpm for ultrafine grinding, and then passed through a 400 mesh sieve, and then added into 30 mL of the above ethanol solution, and after ultrasonic dispersion, 100 mL of hydrochloric acid solution (1 mol / L) is added while stirring, and the pH is adjusted to 3.5, and then 1 mL of γ-aminopropyltriethoxysilane is added, and the mixture is stirred at a constant temperature of 75°C and 250 rpm for 10 hours, and then centrifuged, and the precipitate is collected and dried to obtain modified montmorillonite;
[0057] (2) Dissolve 1 g of chitosan in 100 mL of 1% glacial acetic acid solution, adjust the pH to 4.5, add 1% tannic acid solution (3.5 mg / mL), stir at 250 rpm for 25 min, add 1% titanium tetrachloride solution (0.25 mol / L), stir at 700 rpm for 2.5 h, let stand for 5.5 h, filter, wash with deionized water 4 times, and freeze-dry to obtain modified chitosan for later use;
[0058] (3) Dissolve 1 g of modified chitosan in 100 mL of 1% glacial acetic acid solution, adjust the pH to 5, ultrasonically disperse 15 g of modified montmorillonite in 450 mL of deionized water to obtain a suspension, drop the modified chitosan glacial acetic acid solution into the modified montmorillonite suspension at a rate of 50 mL / L, stir at 900 rpm for 13 min, heat to 65 ° C and react for 19 h, filter after the reaction is completed, wash with deionized water until the pH is neutral, filter, and then place in a vacuum drying oven at 55 ° C for 36 h to obtain a chitosan-montmorillonite composite;
[0059] The volume ratio of the modified chitosan glacial acetic acid solution to the modified montmorillonite suspension is 1:2.5;
[0060] (4) The chitosan-montmorillonite composite was refluxed in an aqueous solution of phosphotungstic heteropolyacid for 9 h, filtered, and the filter cake was washed with deionized water until neutral, and then dried at 45°C in a vacuum drying chamber for 36 h, and then calcined at 200°C for 2.5 h to obtain the desired supported heteropolyacid catalyst.
[0061] Example 3
[0062] A production process of o-nitrochlorobenzene comprises the following steps:
[0063] S1, adding the supported heteropoly acid catalyst, chlorobenzene, carbon tetrachloride and nitrating agent into a three-necked flask in sequence, reacting at a constant temperature of 45°C for 6 hours, cooling to room temperature after the reaction, and separating the supported heteropoly acid catalyst by vacuum filtration;
[0064] The nitrating agent is sulfuric acid-nitric acid-phosphoric acid, and the ratio of sulfuric acid, nitric acid and phosphoric acid is 2:2:6;
[0065] The ratio of chlorobenzene, nitrating agent and carbon tetrachloride is 1:2:8;
[0066] The weight volume ratio of the supported heteropolyacid catalyst to the nitrating agent is 1 g:20 mL;
[0067] S2. Allow the layers to stand and separate, wash the organic layer with a 5% NaHCO3 aqueous solution until it becomes neutral, dry it in a vacuum drying oven at 60°C until it becomes constant weight, separate and crystallize to obtain o-nitrochlorobenzene.
[0068] The preparation of the supported heteropolyacid catalyst described in step S1 comprises the following steps:
[0069] (1) Anhydrous ethanol and deionized water are prepared into an ethanol solution in a ratio of 5:1, 1 g of montmorillonite is added into an ultrafine grinder at 6000 rpm for ultrafine grinding, and then passed through a 400 mesh sieve, and then added into 30 mL of the above ethanol solution, and after ultrasonic dispersion, 100 mL of hydrochloric acid solution (1 mol / L) is added while stirring, and the pH is adjusted to 4, and then 1 mL of γ-aminopropyltriethoxysilane is added, and the mixture is stirred at a constant temperature of 80°C and 300 rpm for 12 h, and then centrifuged, and the precipitate is collected and dried to obtain modified montmorillonite;
[0070] (2) Dissolve 1 g of chitosan in 100 mL of 1% glacial acetic acid solution, adjust the pH to 4.5, add 1% tannic acid solution (4 mg / mL), stir at 300 rpm for 30 min, add 1% titanium tetrachloride solution (0.3 mol / L), stir at 800 rpm for 3 h, let stand for 6 h, filter, wash with deionized water 5 times, and freeze-dry to obtain modified chitosan for later use;
[0071] (3) Dissolve 1 g of modified chitosan in 100 mL of 1% glacial acetic acid solution, adjust the pH to 5, ultrasonically disperse 15 g of modified montmorillonite in 450 mL of deionized water to obtain a suspension, drop the modified chitosan glacial acetic acid solution into the modified montmorillonite suspension at a rate of 50 mL / L, stir at 1000 rpm for 16 min, heat to 70° C. and react for 20 h. After the reaction is completed, filter and wash with deionized water until the pH is neutral, filter and then place in a vacuum drying oven at 60° C. and dry for 48 h to obtain a chitosan-montmorillonite composite;
[0072] The volume ratio of the modified chitosan glacial acetic acid solution to the modified montmorillonite suspension is 1:3;
[0073] (4) The chitosan-montmorillonite composite was refluxed and adsorbed in an aqueous solution of phosphotungstic heteropolyacid for 10 h, filtered, and the filter cake was washed with deionized water until neutral, and then dried at 50° C. in a vacuum drying chamber for 48 h, and then calcined at 200° C. for 3 h to obtain the desired supported heteropolyacid catalyst.
[0074] Comparative Example 1
[0075] A production process of o-nitrochlorobenzene comprises the following steps:
[0076] S1. Add the supported heteropoly acid catalyst, chlorobenzene, carbon tetrachloride and nitrating agent into a three-necked flask in sequence, and react at a constant temperature of 40° C. for 5 h. After the reaction is completed, cool to room temperature and separate the supported heteropoly acid catalyst by vacuum filtration;
[0077] The nitrating agent is sulfuric acid-nitric acid-phosphoric acid, and the ratio of sulfuric acid, nitric acid and phosphoric acid is 2:2:6;
[0078] The ratio of chlorobenzene, nitrating agent and carbon tetrachloride is 1:2:6;
[0079] The weight volume ratio of the supported heteropolyacid catalyst to the nitrating agent is 1 g:10 mL;
[0080] S2. Allow the layers to stand and separate, wash the organic layer with a 5% NaHCO3 aqueous solution until it becomes neutral, dry it in a vacuum drying oven at 55°C until it becomes constant weight, separate and crystallize to obtain o-nitrochlorobenzene.
[0081] The preparation of the supported heteropolyacid catalyst described in step S1 comprises the following steps:
[0082] (1) Dissolve 1 g of chitosan in 100 mL of 1% glacial acetic acid solution, adjust the pH to 4.5, add 1% tannic acid solution (3.5 mg / mL), stir at 250 rpm for 25 min, add 1% titanium tetrachloride solution (0.25 mol / L), stir at 700 rpm for 2.5 h, let stand for 5.5 h, filter, wash with deionized water 4 times, and freeze-dry to obtain modified chitosan for later use;
[0083] (2) Dissolve 1 g of modified chitosan in 100 mL of 1% glacial acetic acid solution, adjust the pH to 5, ultrasonically disperse 15 g of montmorillonite in 450 mL of deionized water to obtain a suspension, drop the modified chitosan glacial acetic acid solution into the montmorillonite suspension at a rate of 50 mL / L, stir at 900 rpm for 13 min, heat to 65° C. and react for 19 h. After the reaction is completed, filter and wash with deionized water until the pH reaches neutral, filter and then place in a vacuum drying oven at 55° C. and dry for 36 h to obtain a chitosan-montmorillonite composite;
[0084] The volume ratio of the modified chitosan glacial acetic acid solution to the montmorillonite suspension is 1:2.5;
[0085] (34) The chitosan-montmorillonite composite was refluxed in an aqueous solution of phosphotungstic heteropolyacid for 9 h, filtered, and the filter cake was washed with deionized water until neutral. It was then dried in a vacuum drying chamber at 45 °C for 36 h and calcined at 200 °C for 2.5 h to obtain the desired supported heteropolyacid catalyst.
[0086] Comparative Example 2
[0087] A production process of o-nitrochlorobenzene comprises the following steps:
[0088] S1. Add the supported heteropoly acid catalyst, chlorobenzene, carbon tetrachloride and nitrating agent into a three-necked flask in sequence, and react at a constant temperature of 40° C. for 5 h. After the reaction is completed, cool to room temperature and separate the supported heteropoly acid catalyst by vacuum filtration;
[0089] The nitrating agent is sulfuric acid-nitric acid-phosphoric acid, and the ratio of sulfuric acid, nitric acid and phosphoric acid is 2:2:6;
[0090] The ratio of chlorobenzene, nitrating agent and carbon tetrachloride is 1:2:6;
[0091] The weight volume ratio of the supported heteropolyacid catalyst to the nitrating agent is 1 g:10 mL;
[0092] S2. Allow the layers to stand and separate, wash the organic layer with a 5% NaHCO3 aqueous solution until it becomes neutral, dry it in a vacuum drying oven at 55°C until it becomes constant weight, separate and crystallize to obtain o-nitrochlorobenzene.
[0093] The preparation of the supported heteropolyacid catalyst described in step S1 comprises the following steps:
[0094] (1) Anhydrous ethanol and deionized water are prepared into an ethanol solution in a ratio of 5:1, 1 g of montmorillonite is added into an ultrafine grinder at 5500 rpm for ultrafine grinding, and then passed through a 400 mesh sieve, and then added into 30 mL of the above ethanol solution, and after ultrasonic dispersion, 100 mL of hydrochloric acid solution (1 mol / L) is added while stirring, and the pH is adjusted to 3.5, and then 1 mL of γ-aminopropyltriethoxysilane is added, and the mixture is stirred at a constant temperature of 75°C and 250 rpm for 10 hours, and then centrifuged, and the precipitate is collected and dried to obtain modified montmorillonite;
[0095] (2) Dissolve 1 g of chitosan in 100 mL of 1% glacial acetic acid solution, adjust the pH to 5, ultrasonically disperse 15 g of modified montmorillonite in 450 mL of deionized water to obtain a suspension, drop the chitosan glacial acetic acid solution into the modified montmorillonite suspension at a rate of 50 mL / L, stir at 900 rpm for 13 min, heat to 65 ° C and react for 19 h, filter after the reaction is completed, wash with deionized water until the pH is neutral, filter, and then place in a vacuum drying oven at 55 ° C for 36 h to obtain a chitosan-montmorillonite composite;
[0096] The volume ratio of the chitosan glacial acetic acid solution to the modified montmorillonite suspension is 1:2.5;
[0097] (3) The chitosan-montmorillonite composite was refluxed in an aqueous solution of phosphotungstic heteropolyacid for 9 h, filtered, and the filter cake was washed with deionized water until neutral, then dried at 45°C in a vacuum drying chamber for 36 h, and calcined at 200°C for 2.5 h to obtain the desired supported heteropolyacid catalyst.
[0098] Comparative Example 3
[0099] A production process of o-nitrochlorobenzene comprises the following steps:
[0100] S1. Add the supported heteropoly acid catalyst, chlorobenzene, carbon tetrachloride and nitrating agent into a three-necked flask in sequence, and react at a constant temperature of 40° C. for 5 h. After the reaction is completed, cool to room temperature and separate the supported heteropoly acid catalyst by vacuum filtration;
[0101] The nitrating agent is sulfuric acid-nitric acid-phosphoric acid, and the ratio of sulfuric acid, nitric acid and phosphoric acid is 2:2:6;
[0102] The ratio of chlorobenzene, nitrating agent and carbon tetrachloride is 1:2:6;
[0103] The weight volume ratio of the supported heteropolyacid catalyst to the nitrating agent is 1 g:10 mL;
[0104] S2. Allow the layers to stand and separate, wash the organic layer with a 5% NaHCO3 aqueous solution until it becomes neutral, dry it in a vacuum drying oven at 55°C until it becomes constant weight, separate and crystallize to obtain o-nitrochlorobenzene.
[0105] The preparation of the supported heteropolyacid catalyst described in step S1 comprises the following steps:
[0106] (1) Dissolve 1 g of chitosan in 100 mL of 1% glacial acetic acid solution, adjust the pH to 5, ultrasonically disperse 15 g of montmorillonite in 450 mL of deionized water to obtain a suspension, drop the chitosan glacial acetic acid solution into the montmorillonite suspension at a rate of 50 mL / L, stir at 900 rpm for 13 min, heat to 65° C. and react for 19 h. After the reaction is completed, filter and wash with deionized water until the pH reaches neutral, filter and then place in a vacuum drying oven at 55° C. and dry for 36 h to obtain a chitosan-montmorillonite composite;
[0107] The volume ratio of the chitosan glacial acetic acid solution to the montmorillonite suspension is 1:2.5;
[0108] (2) The chitosan-montmorillonite composite was refluxed in an aqueous solution of phosphotungstic heteropolyacid for 9 h, filtered, and the filter cake was washed with deionized water until neutral, and then dried at 45°C in a vacuum drying chamber for 36 h, and then calcined at 200°C for 2.5 h to obtain the desired supported heteropolyacid catalyst.
[0109] Comparative Example 4
[0110] A production process of o-nitrochlorobenzene comprises the following steps:
[0111] S1. Add phosphotungstic heteropoly acid catalyst, chlorobenzene, carbon tetrachloride and nitrating agent into a three-necked flask in sequence, and react at a constant temperature of 40° C. for 5 h. After the reaction is completed, cool to room temperature and separate the supported heteropoly acid catalyst by vacuum filtration;
[0112] The nitrating agent is sulfuric acid-nitric acid-phosphoric acid, and the ratio of sulfuric acid, nitric acid and phosphoric acid is 2:2:6;
[0113] The ratio of chlorobenzene, nitrating agent and carbon tetrachloride is 1:2:6;
[0114] The weight volume ratio of the supported heteropolyacid catalyst to the nitrating agent is 1 g:10 mL;
[0115] S2. Allow the layers to stand and separate, wash the organic layer with a 5% NaHCO3 aqueous solution until it becomes neutral, dry it in a vacuum drying oven at 55°C until it becomes constant weight, separate and crystallize to obtain o-nitrochlorobenzene.
[0116] 1. Effect of each production process on chlorobenzene nitration
[0117] The composition and content of chlorobenzene nitration products were determined by liquid chromatography.
[0118] The specific test comparison data are shown in Table 1 below:
[0119] Table 1 Effect of each group of production processes on chlorobenzene nitration
[0120]
[0121] It can be seen from Table 1 above that the yields of Examples 1 to 3 are significantly better than those of the comparative example, reaching 90.86%, and the yield of o-nitrochlorobenzene is 0.95, and the yield of o-nitrochlorobenzene is very high.
[0122] 2. Effect of the weight-to-volume ratio of supported heteropolyacid catalyst to nitrating agent on chlorobenzene nitration
[0123] Based on Example 2, only the weight volume ratio of the supported heteropolyacid catalyst to the nitrating agent was changed, and the rest of the scheme was the same as Example 2. The nitration product of chlorobenzene was tested, and the test results are shown in Table 2 below:
[0124] Table 2 Effect of the weight volume ratio of supported heteropolyacid catalyst to nitrating agent on chlorobenzene nitration
[0125]
[0126] It can be seen from Table 2 above that with the change of the weight volume ratio of the supported heteropolyacid catalyst to the nitrating agent, the ortho-to-to-volume ratio and the yield change greatly, indicating that the supported heteropolyacid catalyst and the nitrating agent can synergistically improve the yield and promote the synthesis of o-nitrochlorobenzene.
[0127] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A production process for o-nitrochlorobenzene, characterized in that: The steps include: S1. Add the supported heteropoly acid catalyst, chlorobenzene, carbon tetrachloride and nitrating agent into a three-necked flask in sequence, and react at a constant temperature of 35-45° C. for 3-6 hours. After the reaction is completed, cool to room temperature and separate the supported heteropoly acid catalyst by vacuum filtration; S2. Allow the mixture to stand for stratification, wash the organic layer with a 5% NaHCO3 aqueous solution until it becomes neutral, and then dry it in a vacuum drying oven until it becomes constant weight, and then separate and crystallize it to obtain o-nitrochlorobenzene.
2. A production process for o-nitrochlorobenzene according to claim 1, characterized in that: The preparation of the supported heteropolyacid catalyst described in step S1 comprises the following steps: (1) Anhydrous ethanol and deionized water are prepared into an ethanol solution in a ratio of 5:1, montmorillonite is added into an ultrafine grinder for ultrafine grinding, and then passed through a 400-mesh sieve, and then added into the above ethanol solution, after ultrasonic dispersion, 1 mol / L hydrochloric acid solution is added while stirring, the pH is adjusted to 3-4, and then γ-aminopropyltriethoxysilane is added, and the mixture is stirred at a constant temperature of 70-80°C and 200-300 rpm for reaction for 8-12 hours, and then centrifuged, and the precipitate is collected and dried to obtain modified montmorillonite; (2) Dissolve chitosan in 1% glacial acetic acid solution, adjust the pH to 4.5, add tannic acid solution, stir at 200-300 rpm for 20-30 min, add titanium tetrachloride solution, stir at 600-800 rpm for 2-3 h, let stand for 5-6 h, filter, wash with deionized water 3-5 times, and freeze-dry to obtain modified chitosan for later use; (3) Dissolve the modified chitosan in 1% glacial acetic acid solution, adjust the pH to 5, ultrasonically disperse the modified montmorillonite in deionized water to obtain a suspension, dropwise add the modified chitosan glacial acetic acid solution to the modified montmorillonite suspension at a rate of 50 mL / L, stir at 800-1000 rpm for 10-16 min, heat to 60-70° C. and react for 18-20 h. After the reaction is completed, filter and wash with deionized water until the pH is neutral, filter and then place in a vacuum drying oven at 50-60° C. and dry for 24-48 h to obtain a chitosan-montmorillonite composite; (4) The chitosan-montmorillonite composite is refluxed in a heteropolyacid aqueous solution for 8 to 10 hours, filtered, and the filter cake is washed with deionized water until neutral, and then dried at 40 to 50° C. in a vacuum drying chamber for 24 to 48 hours, and then calcined at 200° C. for 2 to 3 hours to obtain the desired supported heteropolyacid catalyst.
3. A production process for o-nitrochlorobenzene according to claim 2, characterized in that: The rotation speed during the ultrafine grinding described in step (1) is 5000-6000 rpm.
4. A production process for o-nitrochlorobenzene according to claim 2, characterized in that: The weight volume ratio of the montmorillonite to the ethanol solution in step (1) is 1 g:30 mL; The weight volume ratio of the montmorillonite to the hydrochloric acid solution is 1 g:100 mL; The weight-to-volume ratio of the montmorillonite to gamma-aminopropyltriethoxysilane is 1 g:1 mL.
5. A production process for o-nitrochlorobenzene according to claim 2, characterized in that: The weight volume ratio of chitosan to glacial acetic acid solution in step (2) is 1 g:100 mL; The concentration of the tannic acid solution is 3-4 mg / mL, and the addition amount is 1%; The concentration of the titanium tetrachloride solution is 0.2-0.3 mol / L, and the addition amount is 1%.
6. A production process for o-nitrochlorobenzene according to claim 2, characterized in that: The weight volume ratio of the modified chitosan described in step (3) to the glacial acetic acid solution is 1 g:100 mL; The weight volume ratio of the modified montmorillonite to deionized water is 1 g:30 mL; The volume ratio of the modified chitosan glacial acetic acid solution to the modified montmorillonite suspension is 1:2-3.
7. A production process for o-nitrochlorobenzene according to claim 2, characterized in that: The heteropoly acid described in step (4) is one of phosphotungstic heteropoly acid, phosphomolybdic acid and silicotungstic acid.
8. A production process for o-nitrochlorobenzene according to claim 1, characterized in that: The nitrating agent described in step S1 is sulfuric acid-nitric acid-phosphoric acid, and the ratio of sulfuric acid, nitric acid and phosphoric acid is 2:2:
6.
9. A production process for o-nitrochlorobenzene according to claim 1, characterized in that: The ratio of chlorobenzene, nitrating agent and carbon tetrachloride in step S1 is 1:2:5-8; The weight-to-volume ratio of the supported heteropolyacid catalyst to the nitrating agent is 1 g:2-20 mL.
10. The production process of o-nitrochlorobenzene according to claim 1, characterized in that: The drying temperature in step S2 is 50-60°C.